Chronic hypoxia during gestation enhances uterine arterial myogenic tone via heightened oxidative stress. - Daliao Xiao; Xiang-Qun Hu; Xiaohui Huang; Jianjun Zhou; Sean M Wilson; Shumei Yang; Lubo Zhang (PLoS ONE, 2013)
Chronic hypoxia during gestation has profound adverse effects on the adaptation of uteroplacental circulation in pregnancy. Yet, the underlying mechanisms are not fully understood. The present study tested the hypothesis that enhanced production of reactive oxygen species (ROS) in uterine arteries plays a critical role in the maladaptation of uterine circulation associated with chronic hypoxia. Uterine arteries were isolated from nonpregnant and near-term pregnant sheep maintained at sea level (~300 m) or exposed to high-altitude (3801 m) hypoxia for 110 days. Hypoxia significantly increased ROS production in uterine arteries of pregnant, but not nonpregnant, sheep. This was associated with a significant increase in NADPH oxidase (Nox) 2, but not Nox1 or Nox4, protein abundance and total Nox activity in uterine arteries of pregnant animals. Chronic hypoxia significantly increased pressure-dependent uterine arterial myogenic tone in pregnant sheep, which was abrogated by a Nox inhibitor apocynin. Additionally, the hypoxia-induced increase in myogenic reactivity of uterine arteries to phorbol 12,13-dibutyrate in pregnant sheep was blocked by apocynin and tempol. In consistence with the myogenic responses, the hypoxia-mediated down-regulation of BKCa channel activity in uterine arteries of pregnant animals was reversed by apocynin. The findings suggest that heightened oxidative stress in uterine arteries plays a key role in suppressing the BKCa channel activity, resulting in increased myogenic reactivity and maladaptation of uteroplacental circulation caused by chronic hypoxia during gestation.